Analisis Efektivitas dan Kontribusi Pajak Hotel dan Restoran terhadap Pendapatan Asli Daerah Kabupaten Natuna - Syuparman Syuparman; Mahyus Ekananda; Etty Puji Lestari (Bahtera Inovasi, 2023)
Original Local Government Revenue is an important indicator in determining the level of regional government independence in the fiscal sector. The higher Original Local Government Revenue, more independent the region is in managing the existing potential. This study aims to determine how much the level of effectiveness of hotel taxes and restaurant taxes in Kabupaten Natuna and how big their contribution is to the Original Local Government Revenue of Kabupaten Natuna. The hypothesis put forward in this study that hotel taxes and restaurant taxes have a significant effect on Original Local Government Revenue of Kabupaten Natuna. The test results from this study the level of effectiveness of hotel and restaurant tax revenue in Kabupaten Natuna from 2013 to 2020 is categorized as very effective with an achievement rate of more than 100%. The contribution of hotel tax and restaurant tax the Original Local Government Revenue to Kabupaten Natuna for 2013 to 2020 is very small, with the highest achievement of only 0.84 percent with total revenue of Rp. 3,272,124,202, Partially the hotel tax has a positive effect on Original Local Government Revenue of Kabupaten Natuna, as well as the restaurant tax which has a positive effect on Original Local Government Revenue of Kabupaten Natuna for 2013 to 2020. Simultaneously hotel taxes and restaurant taxes have a positive effect on Original Local Government Revenue of Kabupaten Natuna for 2013 to 2020